Sports injury and illness incidence at the 2021 Summer Universiade: a retrospective study of 6,500 athletes from 113 countries/regions - Zhiwei Li; Shiyun Li; Zhigang Liu; Shunchang Li; Huang Huang; Tutu Wang; Geping Wang (Frontiers in Public Health)
ObjectiveTo provide insights and recommendations for athletes, medical personnel, and event organizers on optimize healthcare services and preventive measures for injuries and illnesses by describing the pattern of injuries and illnesses sustained during the 2021 Summer World University Games.MethodsMedical records of athletes visiting Universiade Athletes’ Village Polyclinic from July 22 to August 10, 2023, were anonymously analyzed to describe the injuries and illnesses sustained.ResultsA total of 478 athletes visited the clinic, including 315 injuries and 163 illnesses. Translating to 9.5 injury visits and 3.1illness visits per 100 athletes. A total of 4.9% of athletes experienced at least one injury, and 2.5% experienced at least one illness. The injuries involved 540 sites, primarily affecting the thighs, shins, knees, lower back, and ankles. Illnesses predominantly involved the respiratory system and digestive system. Thirteen cases of COVID-19, and single cases of H1N1 influenza, malaria, dengue fever, candida intestinal infection, and infectious mononucleosis were detected.ConclusionInjuries and illnesses accounted for 7.4% of the participants. The injury incidence was lower compared to the Summer Olympics and slightly below similar Winter Universiade events, while the illness incidence was higher. Using the electronic medical record visit record data of the hospital information system in the athlete village to study athlete injuries is a method that can be adopted in future large-scale sports events. Taking appropriate infectious disease prevention and control measures can effectively prevent the prevalence of infectious diseases during international large-scale sports events. The athlete village of international large-scale sports events should be equipped with MRI to meet the diagnosis and treatment needs of athletes.